MODEL PEMBELAJARAN MENULIS BERBASIS KEARIFAN LOKAL YANG BERORIENTASI PENDIDIKAN KARAKTER Studi Kuasi Eksperimen pada Siswa SMPN 2 Kelas VII, Windusari, Magelang - Mulyani, Mimi (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This article is underpinned from quasi-experiment research aimed to examine the effectiveness of writing-learning models based on local-cultural wisdom which emphasize on character-building. By comparing studentsâ€™ gain from pretest to posttest in diary writing, it can be shown that the model is very effective in improving students’ ability in writing. Studentsâ€™ability in experiment class increased significantly compares to control class. It can be implied that the local cultural wisdom contributes in the improvement of studentsâ€™ writing ability. Keywords: writing model, local wisdom, character building